Echocardiography and extravascular lung water during 3 weeks of exposure to high altitude in otherwise healthy asthmatics - Saxer, S.; Bader, P. R.; Schneider, S. R.; Mademilov, M.; Sheraliev, U.; Appenzeller, P.; Müller, J.; Sooronbaev, T. M.; Bloch, K. E.; Ulrich, S.; Lichtblau, M. (Frontiers in Physiology, 2023)
Background: Asthma rehabilitation at high altitude is common. Little is known about the acute and subacute cardiopulmonary acclimatization to high altitude in middle-aged asthmatics without other comorbidities. Methods: In this prospective study in lowlander subjects with mostly mild asthma who revealed an asthma control questionnaire score >0.75 and participated in a three-week rehabilitation program, we assessed systolic pulmonary artery pressure (sPAP), cardiac function, and extravascular lung water (EVLW) at 760 m (baseline) by Doppler-echocardiography and on the second (acute) and last day (subacute) at a high altitude clinic in Kyrgyzstan (3100 m). Results: The study included 22 patients (eight male) with a mean age of 44.3 ± 12.4 years, body mass index of 25.8 ± 4.7 kg/m2, a forced expiratory volume in 1 s of 92% ± 19% predicted (post-bronchodilator), and partially uncontrolled asthma. sPAP increased from 21.8 mmHg by mean difference by 7.5 [95% confidence interval 3.9 to 10.5] mmHg (p < 0.001) during acute exposure and by 4.8 [1.0 to 8.6] mmHg (p = 0.014) during subacute exposure. The right-ventricular-to-pulmonary-artery coupling expressed by TAPSE/sPAP decreased from 1.1 by −0.2 [−0.3 to −0.1] mm/mmHg (p < 0.001) during acute exposure and by −0.2 [−0.3 to −0.1] mm/mmHg (p = 0.002) during subacute exposure, accordingly. EVLW significantly increased from baseline (1.3 ± 1.8) to acute hypoxia (5.5 ± 3.5, p < 0.001) but showed no difference after 3 weeks (2.0 ± 1.8). Conclusion: In otherwise healthy asthmatics, acute exposure to hypoxia at high altitude increases pulmonary artery pressure (PAP) and EVLW. During subacute exposure, PAP remains increased, but EVLW returns to baseline values, suggesting compensatory mechanisms that contribute to EVLW homeostasis during acclimatization.